Motivational factors for youth recruitment in voluntary interventions: the case of a community sport program. Issue 7 (2nd October 2016) - Plante, Catherine; Moreau, Nicolas; Jaimes, Annie; Turbide, Carole
Abstract : Recruitment is known to be a challenge for intervention programs targeting youths, including sports programs. Following the popularity of the Alter-Action program of the Montreal-based organization DesÉquilibres, we wanted to understand the motivations and barriers to youths' recruitment in this voluntary sports community program. A qualitative methodology was favored. We conducted 27 semi-structured interviews ( n = 27) with participants, 5 ( n = 5) with the partners, and we carried out a focus group with 5 ( n = 5) of the organization's service practitioners. We also conducted a participant observation with youth cohorts and during preparatory meetings. Five factors influencing recruitment emerged: (1) socialization/belonging; (2) training/physical aspects; (3) 'extraordinary' dimension; (4) practicality of the program; and (5) social influences. Four key elements thus appear important to consider when promoting the recruitment of youths in voluntary community programs: (1) favoring social interactions; (2) insisting on the specific and beneficial elements of the program; (3) allowing youths to experiment a trial period; and (4) including testimonies of former participants in the information session. Further recommendations for psychosocial intervention programs targeting youths are discussed in this article.